Relationship Between Patients' "Sense of Participation" in Healthcare and Their Satisfaction A Survey of 5 Hospitals - Koki Hirata MD, PhD; Yosuke Hatakeyama PhD; Ryo Onishi PhD; Kanako Seto PhD; Kunichika Matsumoto PhD; Shigeru Fujita PhD; Yoji Nagai MD, PhD; Shuhei Iida MD, PhD; Tomonori Hasegawa MD, PhD (SAGE Publishing, 2024)
Patient participation is considered important for the safety and quality of care. The patient's perception of actually being able to participate in healthcare, namely, the sense of participation, may influence patient satisfaction (PS). This study aimed to quantitatively determine the relationship between sense of participation to healthcare and PS. A questionnaire survey was conducted among 100 inpatients from each of the 5 target hospitals. The questionnaire included 6 PS items and 4 patient achievement goals, which were indicators of whether the patients had a sense of participation. The response rate was 60.6% (303/500). Patients who perceived that they could choose a treatment that reflected their values and wishes had significantly higher scores on all PS items. Patients who achieved the goal of "I want to be a member of the medical team and participate actively in treatment and safety activities" showed significantly higher PS related to coping to reduce pain and symptoms. Additionally, patients who achieved the goal of "I believe I am able to voluntarily learn about the disease/treatment and use it to make decisions" had significantly higher PS related to psychological support. Sense of participation may improve PS in a wide range of areas. Hospitals and healthcare workers are expected to empower patients to develop a sense of participation.